2021
DOI: 10.3390/cancers13020272
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Deprivation Induces AKT-AADAT Signaling and Overcomes EGFR-TKIs Resistance in EGFR-Mutant Non-Small Cell Lung Cancer Cells

Abstract: Epidermal growth factor receptor (EGFR) mutations are the most common driver genes in non-small cell lung cancer (NSCLC), especially in the Asian population. Although EGFR-tyrosine kinase inhibitors (TKIs) are influential in the treatment of EGFR-mutant NSCLC patients, acquired resistance inevitably occurs. Therefore, there is an urgent need to develop strategies to overcome this resistance. In addition, cancer cells with particular mutations appear more vulnerable to deficiency related to the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This metabolite is a potential modulator of glucose homeostasis; moreover, it has been identified as a marker of tumor aggressiveness in glioblastoma [ 43 ] and is altered in TNBC cell lines after administration of PARP inhibitor Veliparib [ 44 ]. In fact, it has been demonstrated that lysine metabolism is a relevant process in cancer [ 45 , 46 ]. Other interesting findings are the differences in phenylalanine production ( p -value = 8.36 × 10 −20 ), a protective amino acid against cancer [ 47 ] or capric acid ( p -value = 2.21 × 10 −12 ), a non-competitive AMPA receptor antagonist, responsible for the mitochondrial proliferation, that has been associated with overall breast cancer risk [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite is a potential modulator of glucose homeostasis; moreover, it has been identified as a marker of tumor aggressiveness in glioblastoma [ 43 ] and is altered in TNBC cell lines after administration of PARP inhibitor Veliparib [ 44 ]. In fact, it has been demonstrated that lysine metabolism is a relevant process in cancer [ 45 , 46 ]. Other interesting findings are the differences in phenylalanine production ( p -value = 8.36 × 10 −20 ), a protective amino acid against cancer [ 47 ] or capric acid ( p -value = 2.21 × 10 −12 ), a non-competitive AMPA receptor antagonist, responsible for the mitochondrial proliferation, that has been associated with overall breast cancer risk [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the trained macrophages in PVM-OVA group had a large number of metabolites, such as amino acids, phospholipids, isocitrate, and so on. Amino acids play a vital role in the physiological/metabolic functions of humans, and the abnormal metabolism of amino acids is related to many human diseases, including asthma ( 52 ) and cancer ( 53 ). The increase of certain amino acids such as cysteine and serine in asthmatic patients leads directly or indirectly to the onset of asthma ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, previous studies revealed that genomic alterations of driver genes are infrequent in LEC 4,16,17 . In addition to genomic alterations, aspects of the tumor microenvironment such as the immune microenvironment, molecules, and nutrient availability have been reported to correlate with the clinical outcome and drug sensitivity in this particular type of lung cancer [18][19][20][21] . However, the immune microenvironment of LEC is still largely unknown, and its relationship with clinical outcomes is intriguing to investigate.…”
Section: Introductionmentioning
confidence: 99%